2014
DOI: 10.7150/ijms.7384
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Ultrasound Appearance of Pelvic Floor in Nulliparous Women and Postpartum Women One Week after Their First Delivery

Abstract: This study investigated the morphology and structure of pelvic floor in 50 nulliparous and 95 postpartum women (47 vaginal delivery, 48 Cesarean section) using translabial three-dimensional (3D) ultrasound. All the primiparae underwent ultrasound examination within one week after their first delivery. Volume datasets were acquired and analyzed to determine the alterations of levator hiatus after childbirth. Significant differences were observed in the levator hiatus of postpartum women compared with that of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…A total of 23 studies involving 1207 women who were only delivered by CS contributed data for this outcome 9,13,21–25,27,28,31–33,35,39–44,49,51,53,54 . All the studies reported no LAs with the exception of Araujo et al., 43 Guedea et al 32 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 23 studies involving 1207 women who were only delivered by CS contributed data for this outcome 9,13,21–25,27,28,31–33,35,39–44,49,51,53,54 . All the studies reported no LAs with the exception of Araujo et al., 43 Guedea et al 32 .…”
Section: Resultsmentioning
confidence: 99%
“…For this analysis, only studies that reported on the two compared modalities were included. A total of 12 studies involving 1570 women reported on LA following spontaneous delivery and CS at first birth 9,21,24,28,31–33,39,41,44,51,53 . The calculated odds ratio for having an LA following a spontaneous delivery compared with CS was 10.69 (5.44–21.0, I 2 = 0%) (Figure 3, Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies investigating the changes of the pelvic floor during pregnancy showed that these changes already occur in the course of pregnancy. Most studies started their analysis in pregnancy and compared pelvic floor measurements between mid and late pregnancy and after delivery 8,13–20 . No study published till date has characterized the pelvic floor before, during, and after pregnancy in the same collective.…”
mentioning
confidence: 99%